Keanekaragaman Teripang (Holothuroidea) di Perairan Bagian Timur Pantai Natuna Kepulauan Riau - Sukmiwati, Mery; Salmah, Siti; Ibrahim, Sanusi; Handayani, Dian; Purwati, Pradina (Jurnal Natur Indonesia, 2012)
This study was aimed to investigate diversity of sea cucumber. Samples were collected  in  the coastal  waters  of  Natuna,  Riau  Islands  in  June 2009. Samples were taken from 2 locations: Sepempang and Pengadah beach. Sampling was done by using a transect quadrant of 5x5 m. This  sampling and observation on  its  microhabitat  were conducted by snorkeling. Analyses on the sea cucumber community structure were based on its diversity, equitability, density and frequency of occurance. The result showed that at both  locations there  are 16  species from two families: Holothuriidae and  Stichopodidae.  The higher  diversity index  (H) was  3.256  and  equitability  index  (e) was 0.993.  The higher  density  of species were 0.0032 ind/m2. The higher frequency of occurance was 27.71% by H. atra.